Crossing Borders Between Languages: The Great Transition of Hindi Literary Translation with Special Reference to Geetanjali Shree’s Tomb of Sand - DONGWON LEE (The Journal of Indian and Asian Studies)
The surging number of Hindi speakers in recent decades raises an intriguing question: does the expanding influence of Hindi across India lead to the commensurate pan-Indianization or globalization of its literature? Despite its widespread use within the country, Hindi literature often remains overshadowed by Indian English literature (IEL), particularly on the global stage. It appears to be somewhat confined within regional boundaries. However, a transformative event occurred in 2022 when Geetanjali Shree, a Delhi-based Hindi novelist, clinched the prestigious International Booker Prize for her work, Tomb of Sand, originally titled Ret Samadhi in Hindi. The prize was equally shared between Geetanjali Shree, the writer, and Daisy Rockwell, the translator. With this award, Tomb of Sand has emerged as a symbol of Hindi literary translation, heralding a significant transition in the Hindi literary translation scene. This paper aims to explore the challenges and prospects of Hindi literary translation in the era of the great transition, focusing specifically on the translation methods and strategies employed in Tomb of Sand. Through this analysis, I intend to contribute to the ongoing scholarly discourse concerning the promotion and appreciation of Hindi literature in international literary circles.